Total penile amputation following ritual circumcision: A case report of a devastating complication - Saad Andaloussi; Zakarya Alami Hassani; Saad Annattah; Omar Dalero; Aziz Elmadi (Urology Case Reports)
Circumcision is among the most commonly performed surgical procedures in boys. In Morocco, this practice is often carried out by traditional practitioners, exposing patients to potentially catastrophic complications that are challenging to manage. We report the case of a 2-year-old boy who underwent ritual circumcision complicated by total penile amputation, with loss of the amputated stump. A meatoplasty was performed, and the postoperative course was uneventful. This case underscores the importance of recognizing circumcision as a surgical procedure that should not be trivialized. Furthermore, it highlights the necessity of implementing training programs for traditional practitioners to promote safe circumcision practices.